Thermo-hydraulics of nuclear reactors - Brennen, Christopher E. 1941- (Cambridge University Press, 2016)
"This book provides a concise and up-to-date summary of the essential thermo-hydraulic analyses and design principles of nuclear reactors for electricity generation. Beginning with the basic nuclear physics, it leads through technical and quantitative analyses to descriptions of both the normal operation of the various modern nuclear reactor designs and the analyses of the possible departures from normal operation"--